Identification of Single-Nucleotide Polymorphisms in B3GAT2, CPQ, and HPSE Genes in the Liver Tissue of Arian Broilers with Ascites using RNA-seq Data - Somayeh Hassnvand; Ayoub Farhadi; Elham Yonesi; Ghodrat Rahimimianji; Karim Hasan Pur (پژوهشهای تولیدات دامی)
Extended Abstract Background: Broiler chickens are one of the important and strategic sources in the meat supply of Iran. The main origin of this vital industry is the line chicken, benefiting only a few countries. Iran is one of the countries with a broiler line called Arian. However, this line has not been able to satisfy customers due to some problems, including the high death rate due to the ascites syndrome, a key factor of mortality and losses in the poultry industry. Therefore, it seems necessary to pay attention to a sustainable solution to reduce this disease in the broiler farms of Iran. This syndrome involves different tissues, and an important tissue is the liver, which plays the main role in regulating metabolism in the whole body. The sustainable solution to reduce this syndrome in broiler farms is to create lines resistant to the ascites syndrome through breeding. The present study aimed to identify single-nucleotide polymorphisms (SNPs) in CPQ, B3AGT2, and HPSE genes in the liver tissue of Arain broiler chickens with ascites syndrome using RNA-seq data. Methods: This research was conducted in two phases, including the first phase (ascites induction) and the second phase (normal rearing conditions). In the first phase, 817 one-day-old chicks from 71 paternal stepfamilies from the B Arian line, which were sexed and numbered on the first day, were obtained from the Arian line chickens located in the Babolkanar farms in Mazandaran province and were reared at the Khalat Pushan Poultry Breeding Station at Tabriz University. The birds that showed signs of ascites were classified as susceptible to ascites, and the rest of the birds were classified as healthy. Total RNA from the liver tissue was extracted from 32 birds, including 16 healthy (8 males and 8 females) and 16 diseased (8 males and 8 females) birds individually. An equal amount of RNA from four birds was merged with each other to obtain a total of eight merged samples, four samples from each of healthy and ascites-affected birds. The quantity and quality of the extracted RNA were measured by a UV-1800/SHIMMADZU nanodrop and 1.5% agarose gel. Then, the extracted RNA was treated and purified by DNase. The samples were sequenced using Illumina sequencing technology. The quality of the reads was controlled using FASTQC software, and the reads were aligned using STAR software. After aligning the sequences against the reference genome, the tools provided in two software packages, Picard tools, and GATK, were used to identify the variants in each sample. Results: All the quality control indicators of FASTQC software showed the appropriate quality of the studied data. After quality control, the RNA-seq data of the liver tissue were mapped on the reference genome. About 90% of the reads were mapped on the reference genome, which indicates the high quality of the sequenced data alignment compared to the reference genome. Based on previous reports, the CPQ gene was considered an important gene related to ascites in this study. To fully understand the importance of this gene in disease-related phenotypes, the gene network, and protein interaction with other proteins, the protein network of this gene was drawn based on STRING. The ontology (GO) of 49 genes related to each other based on the string was performed in DAVID software. According to our observation, CPQ, HPSE, and B3GAT2 genes are involved in important biological pathways related to ascites disease. Then, the genes related to CPQ, B3GAT2, and HPSE genes, which were also related to ascites and contained SNPs in the samples with ascites, were selected and studied in this step. In this study, eight and three SNPs were detected in the CPQ gene in the samples with ascites and healthy samples, respectively, which were identified and reported for the first time in this study. The CPQ gene is the most prominent ascites candidate gene identified to date, which can be used in marker-assisted selection to increase ascites resistance in breeding programs. Moreover, four and one SNPs were detected in HPSE and B3GAT2 genes in ascites samples, respectively. However, no polymorphism was found for these genes in healthy samples. Heparanase (HPSE) is an endoglycosidase that catalyzes the cleavage of side chains of heparan sulfate proteoglycans. Therefore, it plays a role in the regeneration of extracellular matrix and basement membranes, as well as the release of various molecules related to heparan sulfate as growth factors, cytokines, and enzymes. Conclusion: The polymorphisms identified in this research can be used to select ascites-resistant lines of broiler chickens in breeding programs by further investigating and confirming their effects on ascites.